Development of a tissue-engineered skin substitute on a base of human amniotic membrane. (January 2019) - John, Samuel; Kesting, Marco Rainer; Paulitschke, Philipp; Stöckelhuber, Mechthild; von Bomhard, Achim
Allogenic graft material and tissue engineering have recently shown promising results for the improvement of both esthetic and functional outcomes in the treatment of large skin defects. We chose human amniotic membrane as a cellular scaffold in order to develop a skin substitute for later in vivo uses. Various methods of de-epithelialization of the human amniotic membrane were evaluated by histological analysis including hematoxylin–eosin and laminin staining, optic coherence tomography, and scanning electron microscopy with 0.25/0.02% trypsin/ethylenediaminetetraacetic acid treatment and mechanical cell removal showing an almost complete loss of the epithelium and a mainly intact basement membrane. Novel examination of human amniotic membrane by optic coherence tomography was feasible, but difficulties were experienced in handling and interpretation of the tissue as no comparable data exist. Subsequently, we developed an air–liquid interface cell culture to cultivate keratinocytes and fibroblasts on the de-epithelialized human amniotic membrane. We achieved a mostly keratinized surface on the epidermal side with a confluent fibroblast network on the chorion side.